The effect of the peer support intervention on internalized stigma among Thai patients with tuberculosis: A repeated measures design - Vibulchai, Nisakorn; Dana, Kamthorn; Sanchan, Monruedee; Churari, Charanya; Jadboonnak, Bunjong; Sawangsri, Wattana; Pothiporn, Wansu Taweekanachote; Sutthicharoen, Udomlak (Belitung Raya Foundation, Indonesia, 2024)
Background: Internalized stigma among patients with tuberculosis (TB) significantly affects delayed diagnosis, increased disease transmission, and poor treatment outcomes. However, conclusive empirical evidence on psychosocial interventions to reduce internalized stigma among patients with TB in Thailand remains scarce. Objective: This study aimed to examine the impact of a peer support intervention on reducing internalized stigma among patients with TB in Thailand. Methods: A one-group within-subjects repeated-measure design was conducted in the Muang Maha Sarakham district, Thailand, from February 2023 to July 2023. The study included 26 participants who met specified criteria. Measurements were taken at baseline, three months, and six months following TB diagnosis and medication treatment. The peer support intervention comprised TB health education, psycho-educational sessions, self-management support, and home visits. The Internalized Stigma of Tuberculosis Scale Thai Version was used to measure internalized stigma. Statistical analyses included descriptive statistics and repeated measures ANOVA. Results: Mean scores of total internalized stigma and its sub-dimensions (alienation, stereotype endorsement, discrimination experience, social withdrawal, and stigma resistance) differed significantly across the three-time points (p <0.001, p <0.001, p <0.001, p <0.001, p <0.001, p = 0.002, respectively). Furthermore, stigma resistance scores significantly increased from pre-intervention to three months (p = 0.005) and from pre-intervention to six months (p = 0.007). However, no significant increase was observed from three to six months (p = 0.079). Conclusions: The study underlines the positive impact of peer support intervention in reducing internalized stigma among patients with TB in Thailand over time. The findings suggest that interventions focusing on peer support can potentially address internalized stigma, highlighting the importance of integrating these strategies into healthcare practices to enhance patient care and improve TB management outcomes.